Comparative Analysis of CXCR5 Circulating DNA Methylation Levels in Autoimmune Rheumatic Diseases - Yiming Shi; Yingying Qin; Yunshen Li; Ping Jiang; Kai Wei; Jianan Zhao; Yu Shan; Yixin Zheng; Fuyu Zhao; Mi Zhou; Li Li; Yu Shen; et al. (Immunity, Inflammation and Disease)
ABSTRACT Objective To assess CXC chemokine receptor 5 (CXCR5) circulating DNA methylation differences in autoimmune rheumatic diseases and their relation with clinical features. Methods Targeted methylation sequencing was performed using peripheral blood from 164 rheumatoid arthritis (RA), 30 systemic lupus erythematosus (SLE), 30 ankylosing spondylitis (AS), 30 psoriatic arthritis (PsA), 24 Sjögren's syndrome (SS) patients, and 30 healthy controls (HC). Results Significant differences in CXCR5 cg19599951 methylation were found between RA and HC, as well as AS and SLE. RA patients exhibited higher methylation than HC and AS (p < 0.01) but lower than SLE (p < 0.05). SLE patients showed higher methylation compared to HC, AS, and PsA (p < 0.001, 0.01, and 0.05, respectively). No significant differences were found in patients with SS compared to other autoimmune diseases and HC. Methylation at cg19599951_103 (r = 0.17, p < 0.05) and cg19599951_209 (r = 0.22, p < 0.01), along with the CC haplotype (r = 0.21, p < 0.01), showed significant positive correlations with erythrocyte sedimentation rate (ESR), while the CT (r = −0.27, p < 0.001) and TT haplotypes (r = −0.19, p < 0.05) were negatively correlated. For C‐reactive protein (CRP), methylation at cg19599951_103 (r = 0.29, p < 0.001) and cg19599951_209 (r = 0.33, p < 0.0001), and the CC haplotype (r = 0.34, p < 0.0001) was positively correlated, whereas the CT (r = −0.36, p < 0.0001) and TT (r = −0.30, p < 0.0001) haplotypes were negatively correlated. Significant negative correlations were observed between the CT haplotype and rheumatoid factor (r = −0.25, p < 0.01), and anti‐citrullinated protein antibody (r = −0.20, p < 0.05). No significant correlations were found in patients with SLE, AS, and SS. Receiver operating characteristic analysis showed CXCR5 methylation could classify patients with RA versus those with AS (AUC: 0.624−0.967). Conclusion Differential circulating CXCR5 methylation levels were observed in autoimmune rheumatic diseases, which correlated with inflammatory mediators in RA and may serve as potential biomarkers for RA diagnosis.